Peru 1950-2010: chronic malnutrition and economic growth in the regional development - Sifuentes León, Eudosio (2012)
To more economic growth, less chronic malnutrition? What factors determine the persistent association between extractive economies and prevalence of chronic malnutrition? The answer to these questions is made taking as the unit of analysis the regions in Peru from 1950 to 2010. It is considered a sample of five regions: Ancash, Cajamarca, Huancavelica extractive mining and agricultural tradition, and Lambayeque to Ica economy based on agribusiness, manufacturing and trade. The study shows, in the period, parallel processes and identify a complex range of social determinants between the continued growth and a tendency to decrease in chronic malnutrition, but with different speeds in the regions over the past decade envisioning opening an epidemiological transition in nutrition. It uses information from the INEI, ENDES, project evaluations, research reports and interviews with mothers of young children in urban and rural communities in the selected regions.